2019
DOI: 10.1093/nsr/nwz129
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in chromium nitrides Pr3Cr10-xN11 with strong electron correlations

Abstract: Exploration of superconductivity in Cr-based compounds has attracted considerable interest because only a few Cr-based superconductors (CrAs, A2Cr3As3 and ACr3As3 (A = K, Rb, Cs, Na)) have been discovered so far and they show an unconventional pairing mechanism. We report the discovery of bulk superconductivity at 5.25 K in chromium nitride in Pr3Cr10-xN11 with a cubic lattice structure. A relatively large upper critical field of Hc2(0) ∼ 12.6 T is determined, which is larger than the estimated Pauli-paramagne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…This belief has been very recently corroborated by the discovery of bulk superconductivity in chromium nitrides La 3 Cr 10−x N 11 [64] and Pr 3 Cr 10−x N 11 [65]. Although these materials do not belong to As-chromium pnictides, they are new N-pnictides that share with the materials here discussed predominantly 3d electrons at Fermi level, implying that the superconductivity mainly results from the condensation of these electrons.…”
Section: Quantum Critical Point External Pressurementioning
confidence: 61%
“…This belief has been very recently corroborated by the discovery of bulk superconductivity in chromium nitrides La 3 Cr 10−x N 11 [64] and Pr 3 Cr 10−x N 11 [65]. Although these materials do not belong to As-chromium pnictides, they are new N-pnictides that share with the materials here discussed predominantly 3d electrons at Fermi level, implying that the superconductivity mainly results from the condensation of these electrons.…”
Section: Quantum Critical Point External Pressurementioning
confidence: 61%
“…According to the results of these studies, the connection between the ferromagnetic constituents perpendicular to the crystallization axis in the CrAs junction is antiferromagnetic. Consequently consideration of the InAs-CrAs systems is of substantial interestl [4][5][6][7]. The present paper is devoted to synthesis and structure investigated of InAs-CrAs systems.…”
Section: Introductionmentioning
confidence: 99%
“…Although many interesting studies have been so far reported on these and other similar compounds, both theoretical [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and experimental [26][27][28][29][30][31][32][33][34][35][36], only a limited amount of information on WP single crystal system is until now available [8]. The aim of this paper is to give a contribution to the investigation of the properties of WP compound, providing electronic structure calculations and a consistent description of resistivity measurements from experiments carried out on WP single crystal samples.…”
Section: Introductionmentioning
confidence: 99%